An Enhanced Model For E-Service Quality of Mobile Banking (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The increasing growth in mobile device users and the rapid drop in conventional and mobile data charges have given way for a provision of banking services and mobile banking to be precise. Banks are now extending their services from traditional means of banking to a self-service system. Recently, mobile banking has been growing exponentially, but there is still a lack of confidence by the users because of low e-service quality of mobile banking. Researchers have done many works on mobile banking but were focused more on adoption and user intentions which contributes to the marketing and promotion of mobile banking. Mobile banking has some specific characteristic which makes it different from other web-based e-services. So the previous studies lack specific in-depth mobile banking e-service quality, such as failure to define the e-service quality of mobile banking and identification of mobile banking dimensions. This study identified mobile banking's dimensions and attributes that received less attention and suggested an improved model for mobile banking's electronic service quality.